Influence of high temperatures and solar radiation on accidents on road transport in the summer - I. N. Yakunin (Вестник СибАДИ, 2020)
Introduction. During the hot season, there is a positive relationship between the number of accidents per thousand registered vehicles and the air temperature. At the same time, an increase in the temperature and intensity of solar radiation helps to reduce the braking distance of cars. Consequently, the likely reasons for the increase in the number of accidents is a decrease in the level of driving skills. The purpose of the work is to determine the most significant causes of road accidents in the summer, the degree of their impact on accidents in conditions of high temperature and solar radiation, as well as the impact of climate installations on the increase in accidents. Materials and methods. In order to identify the causes of the increase in accidents, an expert method was used, which consisted in a survey of 28 professional drivers with at least three years of experience. To assess the significance of factors, the reasons for the increase in accidents were ranked according to a four-point system, where the number “1” corresponded to the lowest significance, and the number “4” – the highest. It was also necessary to indicate the increase in the adverse effect as a percentage in certain conditions, compared with comfortable conditions.Results. It is revealed that the main reasons for the increase in the number of accidents committed in the summer are: an increase in traffic speed, an increase in the frequency of maneuvering vehicles, an increase in the number of incorrect decisions and an increase in the reaction time of drivers. The direct effect of solar radiation, along with the effect of high temperatures that go beyond the comfort zone, is the cause of accidents. The use of climate systems leads to redistribution of importance among the reasons for the increase in the number of accidents – increases the number of accidents by increasing the speed and frequency of maneuvering, while reducing the rate of road accidents occurring in bad judgement and increase reaction time of drivers.Practical importance. The research provides a basis for developing measures to reduce accidents on the road in warm weather